Pendapatan dan pembelanjaan pekerja migran wanita: suatu perbandingan antara sektor awam, industri dan jualan - Paim, Laily; Yahaya, Nurizan (Universiti Putra Malaysia Press, 1997)
The purpose of the study was to determine income and expenditure patterns of female migrant workers in Peninsular Malaysia. The 969 workers between 15 - 30 years old chosen as respondents were selected from 5 zones, i.e., north (Perlis, Kedah and Pulau Pinang), central (Perak and Selangor), south (Negeri Sembilan. Melaka and Johor), east (Pahang, Terengganu and Kelantan), and Metropolitan (Kuala Lumpur). Respondents were chosen from the public (41 %), industrial (38%), and sales (21 %) sectors. The results of the study revealed that most of the women were single, young (mean age of 24) and had an educational level of SPM. Chi-Square tests indicated that there was a significant difference in income among women of different sectors, ages, and levels of education. The results of the study also indicated that there was a significant difference in percentage of income spent on food, housing, and transportation among women of different sectors, ages, levels of education, and marital status.